Platelet-rich fibrin for wound healing of palatal donor sites of free gingival grafts: Systematic review and meta-analysis - Gusman, David-Jonathan-Rodrigues (J Clin Exp Dent, 2021)
BACKGROUND: Platelet-rich fibrin (PRF) has been referred to as a second-generation platelet concentrate, associated with improvements on the healing of palatal wounds followed by FGG harvesting. The aim of this systematic review and meta-analysis was to assess the complete wound epithelialization and postoperative pain when PRF was used in palatal wounds following free gingival graft (FGG) harvesting. MATERIAL AND METHODS: PubMed (Medline), EMBASE and Scopus were searched by two independent individuals up to and including March 2020 in order to identify controlled and randomized controlled clinical trials on the use of PRF at palatal donor sites of FGG. The outcomes assessed were epithelialization and postoperative pain. The risk of bias of the included studies was evaluated using Cochrane Collaboration’s domain-based two-part tool. Random effects meta-analyses were conducted with 95% confidence intervals. RESULTS: The search strategy identified 555 potentially eligible articles, of which 6 randomized controlled clinical trials were included. In the qualitative analysis, most studies (83.3%) reported lower postoperative pain in treatment groups, while all studies accessing epithelialization demonstrated earlier complete wound closure in groups treated with PRF. The discomfort and complete re-epithelialization were more favorable in groups PRF when compared to control groups (P<0.00001). CONCLUSIONS: Within the limits of the present study, it can be concluded that the use of PRF for wound healing of palatal donor sites of FGG may decrease postoperative pain and induce earlier complete wound epithelialization. Key words:Wound healing, oral surgery procedures, pain, postoperative.